Reef Sediments Can Act As a Stony Coral Tissue Loss Disease Vector - Studivan, Michael S.; Rossin, Ashley M.; Rubin, Ewelina; Soderberg, Nash; Holstein, Daniel M.; Enochs, Ian C. (Frontiers in Marine Science, 2022)
Stony coral tissue loss disease (SCTLD) was first observed in 2014 near Virginia Key in Miami-Dade County, Florida. Field sampling, lab experiments, and modeling approaches have suggested that reef sediments may play a role in SCTLD transmission, though a positive link has not been tested experimentally. We conducted an ex situ transmission assay using a statistically-independent disease apparatus to test whether reef sediments can transmit SCTLD in the absence of direct contact between diseased and healthy coral tissue. We evaluated two methods of sediment inoculation: batch inoculation of sediments collected from southeast Florida using whole colonies of diseased Montastraea cavernosa, and individual inoculations of sediments following independent, secondary infections of ∼5 cm2 coral fragments. Healthy fragments of the coral species Orbicella faveolata and M. cavernosa were exposed to these diseased sediment treatments, as well as direct disease contact and healthy sediment controls. SCTLD transmission was observed for both batch and individual diseased sediment inoculation treatments, albeit with lower proportions of infected individuals as compared to disease contact controls. The time to onset of lesions was significantly different between species and among disease treatments, with the most striking infections occurring in the individual diseased sediment treatment in under 24 h. Following infection, tissue samples were confirmed for the presence of SCTLD signs via histological examination, and sediment subsamples were analyzed for microbial community variation between treatments, identifying 16 SCTLD indicator taxa in sediments associated with corals experiencing tissue loss. This study demonstrated that reef sediments can indeed transmit SCTLD through indirect exposure between diseased and healthy corals, and adds credence to the assertion that SCTLD transmission occurs via an infectious agent or agents. This study emphasizes the critical need to understand the roles that sediment microbial communities and coastal development activities may have on the persistence of SCTLD throughout the endemic zone, especially in the context of management and conservation strategies in Florida and the wider Caribbean.